2020
DOI: 10.5377/nexo.v33i02.10796
|View full text |Cite
|
Sign up to set email alerts
|

Collection Scoring Models Development and Research Based on the Deductor Analytical Platform

Abstract: This article solves the problem of collection scoring models constructing and researching. The relevance of solving this problem on the intelligent modeling technologies basis: decision trees, logistic regression and neural networks is noted. The initial data for the models was a set of 14 columns and 5779 rows. The models construction was performed in Deductor platform. Each model was tested on the set of 462 records. For all models, the corresponding classification matrix were constructed and the1st and 2nd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Gillier et al proposed that, at major international conferences such as medicine and law, the audience's views on the interpretation of quality assessment were summarized and case studies were conducted, and it was found that there were diferences in the interpretation of the quality assessment standards between audiences and translators. Ismagilov and I interviewed members of the International Conference of Translators, and the study found that audiences and translators place a high value on the accuracy and clarity of translated content [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gillier et al proposed that, at major international conferences such as medicine and law, the audience's views on the interpretation of quality assessment were summarized and case studies were conducted, and it was found that there were diferences in the interpretation of the quality assessment standards between audiences and translators. Ismagilov and I interviewed members of the International Conference of Translators, and the study found that audiences and translators place a high value on the accuracy and clarity of translated content [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…To compare our method with existing collection scoring methods, we collect registration information and repayment records which are used in References 3,4 as many as possible for all the clients in the dataset. A description collected variables is presented in Table 3.…”
Section: Baseline Modelmentioning
confidence: 99%
“…Then machine learning algorithms like Logistic regression, SVM and Decision Trees are embraced to make a prediction based on these data. In Reference 3 , 12 variables are used (age, number of payments before the delay, etc.) to train a logistic regression model to segment overdue clients into groups.…”
Section: Introductionmentioning
confidence: 99%